간호사의 죽음인식이 생명존중의지에 미치는 영향 - 백현진(Hyun Jin Baek); 김숙영(Soukyoung Kim) (한국콘텐츠학회 논문지, 24(3), 2024)
본 연구는 간호사의 죽음인식과 생명존중의지의 수준을 파악하고, 죽음인식이 생명존중의지에 미치는 영향을 알아보기 위하여 시도되었다. 경기도 U 시와 D 광역시 소재 종합병원 2곳에서 근무하는 임상경력 6개월 이상의 간호사 189명을 대상으로 실시된 본 연구에서 죽음의 부정적인 의미는 7점 만점에 4.72(±0.83)점, 긍정적인 의미는 4.39(±0.98)점, 죽음불안은 4.20(±1.20)점, 죽음관여도는 3.96(±0.98)점으로 나타났다. 생명존중의지는 4.72(±1.58)점으로 측정되었다. 생명존중의지에 영향을 미치는 요인을 파악하기 위해 위계적 회귀분석을 실시한 결과 종교, 교육수준, 죽음불안이 유의한 변수인 것으로 나타났다. 연구대상자의 종교가 기독교이거나 석사 이상일수록, 죽음불안이 클수록 생명존중의지가 높은 것으로 나타났다. 본 연구는 간호사의 생명존중의지를 높이기 위한 중재프로그램을 개발하는데 기초자료로 활용할 수 있다. The purpose of this study are to identify the level of nurses' perception of death and respect for life, and to examine the effect of perception of death on the will to respect life. The study was conducted on 189 nurses with clinical experience of six months or more who are working at general two hospitals located in U-City, Gyeonggi Province and D-Metropolitan City. The negative meaning of death was 4.72(±0.83) points out of 7 points, the positive meaning of death was 4.39(±0.98) points, death anxiety 4.20(±1.20) points, death concern 3.96(±0.98) points, and the respect for life was measured at 4.72(±1.58) points. Hierarchical regression analysis was performed to identify the factors affecting the respect for life. As a result, religion, level of education, and death anxiety were found to be significant variables. It was found that the respect for life increased if the subject’s religion was Christian or had a master's degree or higher, or as death anxiety increased. This study can be used as basic data for developing an intervention program to increase nurses' respect for life. KCI Citation Count: 0